Molecular Characterization of Carbonic Anhydrase II (CA II) and Its Potential Involvement in Regulating Shell Formation in the Pacific Abalone, Haliotis discus hannai - Sharker, Md. Rajib; Sukhan, Zahid Parvez; Sumi, Kanij Rukshana; Choi, Sang Ki; Choi, Kap Seong; Kho, Kang Hee (Frontiers in Molecular Biosciences, 2021)
Carbonic anhydrases (CAs) are a family of metalloenzymes that can catalyze the reversible interconversion of CO2/HCO3–, ubiquitously present in both prokaryotes and eukaryotes. In the present study, a CA II (designated as HdhCA II) was sequenced and characterized from the mantle tissue of the Pacific abalone. The complete sequence of HdhCA II was 1,169 bp, encoding a polypeptide of 349 amino acids with a NH2-terminal signal peptide and a CA architectural domain. The predicted protein shared 98.57% and 68.59% sequence identities with CA II of Haliotis gigantea and Haliotis tuberculata, respectively. Two putative N-linked glycosylation motifs and two cysteine residues could potentially form intramolecular disulfide bond present in HdhCA II. The phylogenetic analysis indicated that HdhCA II was placed in a gastropod clade and robustly clustered with CA II of H. gigantea and H. tuberculata. The highest level of HdhCA II mRNA expression was detected in the shell forming mantle tissue. During ontogenesis, the mRNA of HdhCA II was detected in all stages, with larval shell formation stage showing the highest expression level. The in situ hybridization results detected the HdhCA II mRNA expression in the epithelial cells of the dorsal mantle pallial, an area known to express genes involved in the formation of a nacreous layer in the shell. This is the first report of HdhCA II in the Pacific abalone, and the results of this study indicate that this gene might play a role in the shell formation of abalone.